Verständlichkeit und Qualitätskontrolle bei der Gesetzgebung in Krisensituationen in Österreich - Steiner, Wolfgang (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
This article is the written version of the presentation given by the author at the "5th European Symposium on the Comprehensibility of Legal Provisions" on 11 March 2021. In addition to a diagnosis of the (legal) handling of the COVID-19 pandemic in Austria, it presents suggestions for a future management of crisis situations while maintaining the rule of law requirements for the comprehensibility of legal provisions.